2020
DOI: 10.1111/jse.12685
|View full text |Cite
|
Sign up to set email alerts
|

Altitude‐related shift of relative abundance from insect to sunbird pollination in Elaeagnus umbellata (Elaeagnaceae)

Abstract: The evolution of floral traits has been thought to be influenced by local, effective pollinators. However, little attention has been paid to the possibility that altitudinal variation in floral traits could be mediated by local pollinator functional groups, particularly a shift from bees to birds. Plant size, floral traits, pollinators and their pollination roles were investigated in the spring‐flowering shrub Elaeagnus umbellata (Elaeagnaceae) at three altitudes (1160, 1676, and 2050 m) in Minshan, Sichuan Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…This study shows that these traits exist in E. umbellata but suggests that they are rare. However, it has been shown that reproductive strategies can vary greatly across a species' range and may be related to pollinator visitation (Toji & Itino, 2020; Pi et al, 2020). Therefore, it would be beneficial to examine whether these traits are more prevalent on the edge of the range in E. umbellata , where mates and pollinators are most likely to be limited (Levin, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that these traits exist in E. umbellata but suggests that they are rare. However, it has been shown that reproductive strategies can vary greatly across a species' range and may be related to pollinator visitation (Toji & Itino, 2020; Pi et al, 2020). Therefore, it would be beneficial to examine whether these traits are more prevalent on the edge of the range in E. umbellata , where mates and pollinators are most likely to be limited (Levin, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Dipterans and Lepidopterans are the other two important pollinators. Interestingly, although rare, cases of bird pollination were observed in Leucosceptrum canum (Labiatae), whose flowers are open‐shaped with dark purple nectar (Zhang et al, 2012b), Caragana sinica (Pi et al, 2016), Elaeagnus umbellata (Elaeagnaceae, Pi et al, 2021), and large‐flowered Rhododendron species (Huang et al, 2017), and bat pollination in Oroxylum indicum (Bignoniaceae) in the foothills of the Western Himalaya was also observed (Vikas et al, 2009).…”
Section: Pollinator Diversitymentioning
confidence: 99%
“…Later analysis of size variation in pollen aggregation by viscin threads across 13 Rhododendron species confirmed that pollen dispersal units varied with pollinator size (Song et al, 2019). A recent study observed an altitude‐related shift of relative abundance from insect to sunbird pollination in Elaeagnus umbellata (Elaeagnaceae) on the northern rim of the HMR (Pi et al, 2021), providing a first case of pollination ecotype in these mountainous areas. In other mountainous areas, for instance in the Southern Alps in France, along an elevation gradient from 970 to 2700 m, flies were the main potential pollinators above 1500 m; bee and beetle abundance decreased rapidly from this elevation (Lefebvre et al, 2018).…”
Section: Pollinator Diversitymentioning
confidence: 99%
“…Similarly, in a study, noticeable variations in the morphological traits of Boswellia trees in Eritrea were observed. Tree height, crown diameter, and depth all decreased with increasing altitude [65,66]. The number of primary branches was found to be significantly low at 1330 masl, that is, 94.4 and high at 336 masl, that is, 139.8 and maximum number of secondary branches were found at 1330 masl, namely, 122.6.…”
Section: Resultsmentioning
confidence: 99%